Perancangan User Experience Modul Dosen pada Aplikasi Bimbingan Akademik menggunakan metode Design Thinking - Afani Kurniawan; Herman Tolle; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
During lectures, students did not escape the problem, the selection of streams, selection of courses, and so on who needed a supervisor to find a meeting point. Academic guidance activitiy is activity in which academic advisory lecturer and students communicate to solve a problem. But not a small amount of academic advisory lecturer activities carried out every day. Lecturer activities to monitor the development of student lectures also only monitor Course Grades on the lecturer's academic information system. The system has not been able to evaluate student grades. Therefore, the design of the User Experience Module Lecturer in the application of academic guidance will help overcome these problems and make academic guidance activities running well at the Faculty of Computer Science Universitas Brawijaya. The Design Thinking method is used by going through 5 processes, which is empathy to get the views and needs of users, define for defining the needs and problems that exist, ideate to provide a solution design, prototyping high-fidelity design, and testing to measure how useful the application design before being developed to the program code. The results of the testing obtained with usability testing resulted in effectiveness of 88%, efficiency of 86.04.2%, and satisfaction of 85.5. The UEQ method is also done by producing an value of attractiveness 2.30, value of perspicuity 1.85, value of efficiency 2.00, value of 2.45, value of stimulation 2.35, and values of novelty 2.10.